Micromorphological Characteristics of Soils with Andic Properties from Mt. Merbabu and Mt. Tangkuban Perahu, (Central and West Java, Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT: An investigation was conducted to study the micromorphological characteristics of selected soils derived from volcanic materials with a ndic properties from Java (Indonesia). Eight profiles were collected from the surroundings of Mt. Merbabu, in Central Java and Mt. Tangkuban Perahu, in West Java representing soils developed on different parent materials and at different altitudes. Five profiles from Mt. Tangkuban Perahu and three profiles from Mt. Merbabu were compared. The mains micromorphological characteristics of these soils are: spongy and mainly granular microstructure and an incomplete subangular blocky microstructure in the deeper horizons. Pores comprise various types and sizes : vughs, packing voids and channels. Coarse mineral components consist mainly of plagioclase, hypersthene, a ugite, hornblende, rock fragments, phytoliths, tridymite and cristobalite. Volcanic glass grains are frequently noticed in the upper horizons and the amounts decrease in the deeper horizons. The dominant fine material (< 10 mm) is brown to dark brown due to the presence of organic matter. The commonly pedofeatures are : iron nodules and iron staining after weathered minerals, channels in fillings and excremental pedofeatures related to plant remain and biological activities. Mineralogical analyses in soil thin sections show more variety in heavy and light minerals in the toeslopes with larger size and less weathered grain than those in the foot and middle slope. 'Key word : volcanic ash, micromorphology, soil thin section, microstructure. fine materials. pedofeature, heavy and light mineralMicromorphological Characteristics of Soils with Andic Properties from Mt. Merbabu and Mt. Tangkuban Perahu, (Central and West Java, Indonesia) Sri Nuryani Hidayah Utami